Origins and deep petroleum dynamic accumulation in the southwest part of the Bozhong depression, Bohai Bay Basin: Insights from geochemical and geological evidences. (December 2021) - Wang, Qi; Hao, Fang; Niu, Chengming; Zou, Huayao; Miao, Quanyun; Yin, Jie; Cao, Yijin; Liu, Mengxing
Abstract: Latest exploration practices revealed appreciable petroleum resources in the deep pre-Cenozoic reservoirs in the southwest area of the Bozhong depression; however, the origins and accumulation mechanisms of deep hydrocarbons remain not fully understood. Here, an integrated study of the geochemical characteristics of overlying source rocks, maturity evaluation of petroleum, and origin of natural gas was conducted to characterize the dynamic petroleum accumulation and illustrate the main factors influencing the differential phases of petroleum distribution in the research area. The third member of the Dongying Formation (Ed3 ) mudstone in the research area displays high organic richness and is characterized by oil-prone organic matter, indicating high petroleum potential. The oils contained in the CFD18 and BZ13 buried-hill traps were mainly derived from the Ed3 and Shahejie Formation (Es) source rocks, respectively, with natural gas of kerogen cracking origin. Buried-hill oil from the BZ13 field displays a high thermal maturity than that of the CFD18 oils, which was evidenced by maturity parameters of saturated and aromatic hydrocarbons and concentrations of stigmastane. Nevertheless, maturity index of diamondoids and carbon isotopic composition of natural gas indicate the possible presence of mixing of higher mature Es fluids for the CFD18 field. This research underlines the contribution of the overlapped effective source rocks to the buried-hill traps. The causes of multiple petroleum phases in the deep reservoirs in the research area are mainly linked to dynamic petroleum accumulation rather than source rock type and oil secondary cracking. Although faults are present to act as vertical migration conduits due to late-stage activation with high intensity, abundant petroleum supply due to near-source charge and favorable constitution relationship of source rock and reservoir rock provide crucial conditions for deep petroleum accumulation in a tectonic activation zone. Highlights: The origins of deep oil and gas were determined. The cracking degree of deep oil was estimated. Petroleum phase differences reflect dynamic accumulation rather than sourcr rock type and secondacry cracking of oil. Mechanisms of deep petroleum accumulation in a tectonic activation zone were summarized.